E-053 Multi-Modality Management of Posterior Fossa Arteriovenous Malformations: Clinical and Angiographic Outcomes. (26th July 2014) - Robert, T; Blanc, R; Ciccio, G; Gilboa, B; Boissonnet, H; Fahed, R; Redjem, H; Pistocchi, S; Bartolini, B; Piotin, M
Abstract : Background: Infratentorial arteriovenous malformations (AVM) are rare entities, representing only 7–15% of cerebral AVMs. The concentration of eloquent neurological systems and the high rate of bleeding presentation of AVMs in this location complicate the management of such lesions. New therapeutic options, especially in endovascular neurosurgery, have fundamentally modified the strategy and also the outcome of posterior fossa AVMs. Methods: Between 1999 and 2013, baseline, clinical and angiographic data of cerebral AVMs were prospectively collected. We analyzed data from patients treated for a posterior fossa AVM, focusing on risk factors for bleeding, and clinical and angiographic outcomes. Results: Sixty-nine patients (mean age 34 years, male to female ratio: 2) were consecutively treated for an infratentorial AVM. Fifty-seven presented with haemorrhage, 6 with focal neurologic deficits, the 6 cases were diagnosed incidentally. The Spetzler-Martin grade was <3 in 39 (56.5%) cases. Associated aneurysms were noted in 43.5% of cases. All patients had been treated by endovascular procedures, associated with microsurgical resection in 9 patients and with stereotactic radiosurgery in 6 cases. Mean follow-up was 28.5 months, with angiographic exclusion of the AVM in 72.5% of cases; 21.7% of patients presented a modified Rankin Score ≥3 at follow-up. Conclusions: Endovascular embolization is a valid and secure approach for posterior fossa AVMs although a large number of sessions is necessary to achieve complete obliteration. Multi-disciplinary discussion and management is crucial to obtain the best cure rate without increasing procedural risks. Disclosures: T. Robert: None. R. Blanc: None. G. Ciccio: None. B. Gilboa: None. H. Boissonnet: None. R. Fahed: None. H. Redjem: None. S. Pistocchi: None. B. Bartolini: None. M. Piotin: None.